2016
DOI: 10.1515/macvetrev-2016-0090
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Economic Effects in Intesive Production of Piglets

Abstract: Macedonian Veterinary ReviewCritical indicators of intensive production in hog raising are continuity of production, high level of produced series-tours, application of the most contemporary technological achievements without any turnover of capital, high merchandise turnover, and intensive usage of the reproduction potential of breeding material. Production of piglets represents one of the most essential phases in the production of pork meat. In spite of genetic factors, duration of interval wean-conception i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…However, there is one limitation of selection toward c.392G>A, because AA animals presented lowered daily gains. According to current trends in pig breeding, the fattening traits are the most decisive economical features in pig production (Mirilović et al, 2016). Although AA pigs had lower daily gains and the highest age of slaughter, detected differences between opposite homozygotes were low (54 g and 5.8 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is one limitation of selection toward c.392G>A, because AA animals presented lowered daily gains. According to current trends in pig breeding, the fattening traits are the most decisive economical features in pig production (Mirilović et al, 2016). Although AA pigs had lower daily gains and the highest age of slaughter, detected differences between opposite homozygotes were low (54 g and 5.8 days, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A produção moderna industrial de suínos está fortemente atrelada aos desempenhos produtivo e reprodutivo das porcas. Esses, por sua vez, determinam o número de leitões desmamados e consequentemente o número de animais em terminação, culminando na quantidade de carne produzida (MIRILOVIĆ et al, 2016). Portanto, práticas de manejo -especialmente as nutricionais -que visem melhorar a performance das porcas durante a gestação e a maternidade, podem ser determinantes para o sucesso de um lote (CHEN et al, 2019).…”
Section: Introductionunclassified
“…Serbia, 2022), it is evident that economic effectiveness of pig production in Serbia requires additional research.Discussing importance and export potential of Serbian livestock production, Madžar (2014) concluded that there is a decrease in livestock number followed by an increasing import of livestock products. Research covering period from 2001 to 2014(Mirilović et al, 2015) determined that during the observed period there were five years with negative economic performance of pig production(years 2002, 2003, 2006, 2007 and 2010). Having in mind variability of market prices,Zekić et al (2007) stated that pig producers have an uncertain position, while the supply of processing industry is unstable Zekić et al (2008).…”
mentioning
confidence: 99%